Identifying the Needs of Accounting and Financial Students on ESP Material at Vocational High School - Khotimah, Umi Kusnul; Sukmaantara, I Putu; Suharjito, Bambang (English Education Study Program, 2022)
English for Specific Purposes (ESP) ensures designing course to meet learners’ needs. Two points determining the needs are target needs and learning needs as proposed by Hutchinson and Waters (1987). The purpose of this study was to find out the students’ needs of Accounting and Financial Department on ESP Material at Vocational High School. Many studies have been done related to needs analysis at university level. Thefore, this study focused on conducting needs analysis for the students at Vocational High School. This design of this study is survey research. The data were collected through needs analysis questionnaires that given to the tenth grade of Accounting and Financial department which consisted of 20 questions and the semi-structured interview presented for the English teacher and the subject teacher. This research used both qualitative and quantitative information to analyze the data. The results of the students’ responses questionnaire showed that the skill that the students needs for their future career was speaking skill and they also stated that the English materials they learnt did not accordance with their needs. The students were aware of what their needs and wants, therefore, the requirement of ESP materials was improtant for both the English teacher and the students